Whole genome sequencing revealed genetic diversity, population structure, and selective signature of Panou Tibetan sheep - Shi, Huibin; Li, Taotao; Su, Manchun; Wang, Huihui; Li, Qiao; Lang, Xia; Ma, Youji (BMC genomics, 2023)
The detection of selective traits in different populations can not only reveal current mechanisms of artificial selection for breeding, but also provide new insights into phenotypic variation in new varieties and the search for genes associated with important traits. Panou sheep is a cultivated breed of Tibetan sheep in China with stable genetic performance, consistent appearance and fast growth and development after decades of artificial selection and cultivation. Due to long-term adaptation to the high altitude, cold and hypoxic environment in the plateau area, they may have formed a unique gene pool that is different from other Tibetan sheep breeds. To explore the genetic resources of Panou sheep, we used next-generation sequencing technology for the first time to investigate the genome-wide population structure, genetic diversity, and candidate signatures of positive selection in Panou sheep. Comparative genomic analysis with the closely related species Oula sheep (a native breed of Tibetan sheep in China) was used to screen the population selection signal of Panou sheep. Principal component analysis and neighbor joining tree showed that Panou sheep and Oula sheep had differences in population differentiation. Furthermore, analyses of population structure, they came from the same ancestor, and when K = 2, the two populations could be distinguished. Panou sheep exhibit genetic diversity comparable to Oula sheep, as shown by observed heterozygosity, expected heterozygosity and runs of homozygosity. Genome-wide scanning using the Fst and π ratio methods revealed a list of potentially selected related genes in Panou sheep compared to Oula sheep, including histone deacetylase 9 (HDAC9), protein tyrosine kinase 2 (PTK2), microphthalmia-related transcription factor (MITF), vesicular amine transporter 1 (VAT1), trichohyalin-like 1 (TCHHL1), amine oxidase, copper containing 3 (AOC3), interferon-inducible protein 35 (IFI35). The results suggest that traits related to growth and development and plateau adaptation may be selection targets for the domestication and breeding improvement of Tibetan sheep. This study provides the fundamental footprints for Panou sheep breeding and management.